Microbiota-associated immunotherapy resistance caused by deficient PD-L2 - RGMb signaling - Marine Fidelle; Isabelle Lebhar; Laurence Zitvogel; Guido Kroemer (OncoImmunology)
In a recent paper in Nature, Park et al. propose a mechanism through which intestinal dysbiosis compromises the efficacy of immunotherapy targeting the PD-L1/PD−1 interaction. Dysbiosis may upregulate a pair of checkpoint molecules, i.e. PD-L2 interacting with RGMb. Antibodies targeting PD-L2/RGMb can restore responses to PD−1 blockade in the context of dysbiosis.